Qualitative Exploration of Legal, Economic and Health Impacts of Covid-19 in Saudi Arabia - Yusuff Jelili Amuda; Emna Chikhaoui; Shafiqul Hassan; Mohsin Dhali (Emerging Science Journal, 2022)
Since the outbreak of COVID-19, several researches have been conducted in different parts of the world, including Saudi Arabia. However, there is little focus of attention on qualitative exploration of the impacts of COVID-19 in the context of Saudi Arabia. The primary objective of this study was to explore the opinions of legal, economic, and medical experts pertaining to the impacts of COVID-19. The methodology employed in this paper was a qualitative research design. The data was collected with a specific focus on the use of an in-depth interview. Fifteen (15) participants among the legal, economic, and medical experts were finally used for the interview among the targeted participants. In order to analyze the data, different themes were generated from the transcribed interviews, which were: Overview of COVID-19, legal, economic, health impacts. The finding of the study revealed that the current pandemic of Covid-19 has multidimensional impacts in Saudi Arabia. The pandemic has negative impact not only on the social and economic areas but also on the legal sphere. Social and economic impacts of the Covid-19 increase the inequality, discrimination, unemployment, deprivation of usual education, and disruption in business activities. The findings further indicated that the legal impact of COVID-19 has been mentioned in the aspect of the inability to perform contracts that have the potential to trigger default or force majeure provisions leading to litigation or reconciliation. In addition, the participants also acknowledged the health impact of COVID-19 in causing anxiety, suffering from illness, loneliness, depression, and causing death, among others. If not properly addressed through effective measures and policy, the impact of the COVID-19 on the legal, economic, and health spheres would have severe consequences. Therefore, it is recommended that all the stakeholders, especially the government of Saudi Arabia should effectively and efficiently address the legal, economic, and health impacts of COVID-19. Doi: 10.28991/esj-2022-SPER-01 Full Text: PDF